Prader-Willi syndrome : development and manifestations - Whittington, Joyce (Cambridge University Press, 2004)
This book identifies and integrates the latest findings about how best to manage the complex care needs of people with Prader-Willi syndrome (PWS). The data provided by the Cambridge PWS study, the largest and most rounded cohort studies of PWS in the world, is the basis of this book.